PERSEPSI PENGRAJIN BATIK TENTANG PENERAPAN SELF-HELP GROUPS DALAM RANGKA PENGUATAN SENTRA INDUSTRI BATIK - Dewi Prihatini (STIE Mandala Jember, 2013)
The study aims to analyze the perception of the batik craftmen toward self-help groupsthat had been advocated for development and strengthening the center of the batik industry in Tuban District.This study is a descriptive research. The respondents were determined by snowball sampling method consisting of 84 batik craftmen in the batik industry. Both qualitative and quantitative research approaches were used in this study. Aside from the secondary data, the primary data was collected by ethnographic (unstructured and semi-structured interviews, and direct observation) and participatory methods (key informant interviews).The result of the study shows that the perception of the batik craftmen toward the contribution of self-help groups for development and strengthening the center of the batik industry in Tuban District is categorized “moderate”. Therefore, improvement in the aspects of raw materials supply, technology applied, and business management in the business performance of batik industries are still needed.